Waqf Regulation in Indonesia: Implementation of The Waqf Phenomenon in Indonesia Viewed from Legal, Tax, and Supervision Aspects - Mohammad Ridwan (Department of Public Administration, 2023)
The phenomenon of waqf in Indonesia is quite common. This is because most of Indonesia’s population is Muslim, so a lot of wealth is given for the benefit of the community. In its implementation, waqf must be seen from an administrative perspective, including legal laws, taxation, and supervision. This study then aims to see how tax implementation is viewed from these three sides. This research will be carried out using a normative juridical approach. The data used in this study comes from various laws and previous studies which still have relevance to the research discussion. The results of this study then found that the formation of regulations regarding waqf had begun to be implemented before the independence era. Law Number 41 of 2004 concerning waqf forms the basis for waqf law in Indonesia. In general, assets that are part of waqf are not taxed. Meanwhile, the Indonesian Waqf Board (BWI) is generally the supervisor of various affairs regarding waqf in Indonesia